THE INFLUENCE OF SALES FORCE AUTOMATION AND SALES TRAINING ON MEDICAL REPRESENTATIVE PERFORMANCE TO IMPROVE SALES EFFECTIVENESS - Dwi Warni Wahyuningsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This research aims to analyze the influence of sales force automation and sales training on performance medical representative to increase the effectiveness of sales. The population of this research is a multinational pharmaceutical company employee work areas of Yogyakarta and Solo. Sample saturated samples were determined by the respondent, with the whole medical pharmaceutical multinational representative in Yogyakarta and Solo as much as 128 people. The data collection method is used with the kuisoner technique. Engineering analysis using model of causality. The results showed that the influence of the system: there is a sales force automation and sales training on performance medical representative; There is the influence of medical representative's performance against sales effectiveness; There is the influence of the system of sales force automation and sales training sales effectiveness against directly without going through the performance of medical representative in the multinational pharmaceutical companies. Keyword: Sales Force Automation, Sales Training, Performance, Effectiveness Of Sales